Impacts of Capacity Building on Teachers’ Job Performance in Basic Schools in Ilorin West Local Government (Kwasu International Journal of Educational Management and Leadership, 2026)
This study examined the impacts of capacity building on teachers’ job performance in basic schools in Ilorin West Local government, Kwara State. The study adopted descriptive research design of survey type. The population of comprised all the 2,321 teachers in the 45 public lower basic schools in the area. Random sampling technique was used to select 15 schools which represented 33.3%. Proportionate sampling technique was used to select 246 teachers out of the 682 in the sampled schools. Impacts of Capacity Building on Teachers’ Job Performance Questionnaire was used to collect data for the study. The instrument was validated, subjected to reliability test through the use of Cronbach’s Alpha and yielded reliability coefficient of 0.73. Mean and standard deviation, t-test and analysis of variance were used to analyze the data. The study found that there was a significant impact of capacity building on teachers’ job performance in basic schools in Ilorin West Local government, Kwara State. It was recommended that Kwara State government should be more committed to building the capacity of teachers via periodic and constant programmes such as workshops, conferences, seminars, lectures, and sponsorship for further studies, so as to enhance effective job performance of teachers.